2011
DOI: 10.1016/j.envres.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Differences in urine cadmium associations with kidney outcomes based on serum creatinine and cystatin C

Abstract: Cadmium is a well known nephrotoxicant; chronic exposure increases risk for chronic kidney disease. Recently, however, associations between urine cadmium and higher creatinine-based estimated glomerular filtration rate (eGFR) have been reported. Analyses utilizing alternate biomarkers of kidney function allow evaluation of potential mechanisms for these observations. We compared associations of urine cadmium with kidney function measures based on serum cystatin C to those with serum creatinine in 712 lead work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…As previously published, a statistical mechanism related to the use of creatinine in both exposure and outcome metrics is a consideration for these associations. 9 The striking change in urine creatinine associations when a statistically significant metal is in the model, as evidenced by models 1 and 2 (tables 3 and 4), lends support for this mechanism. However, given the differences in associations between metals, unique metal-specific mechanisms, such as metaleprotein binding affecting excretion 48 must also be considered.…”
Section: Discussionmentioning
confidence: 83%
“…As previously published, a statistical mechanism related to the use of creatinine in both exposure and outcome metrics is a consideration for these associations. 9 The striking change in urine creatinine associations when a statistically significant metal is in the model, as evidenced by models 1 and 2 (tables 3 and 4), lends support for this mechanism. However, given the differences in associations between metals, unique metal-specific mechanisms, such as metaleprotein binding affecting excretion 48 must also be considered.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, these metals are potential or known nephrotoxicants (Shelley et al, 2012, 2014; Weaver et al, 2011a, 2011b). However, no consistent evidence of nephrotoxicity was observed in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations between urine nephrotoxicant levels and measures of estimated glomerular filtration rate (eGFR) have been reported recently in a range of populations (de Burbure et al, 2006; Ferraro et al, 2010; Shelley et al, 2012; Weaver et al, 2011b; You et al, 2011). The direction of these associations is contrary to what is expected in nephrotoxicity, despite the fact that some of these toxicants, such as lead and cadmium, have well established nephrotoxic effects.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In that study, the ratio of urine cadmium to urine creatinine was used to adjust for urine dilution. Additional investigations using cystatin C based eGFR measures strongly suggested that the positive association of urine cadmium with kidney function may be a statistical effect related to the use of urine creatinine adjustments and serum creatinine based measures of kidney function (Weaver et al 2011b). …”
Section: Discussionmentioning
confidence: 99%